2004
DOI: 10.1002/hlca.200490245
|View full text |Cite
|
Sign up to set email alerts
|

Hybridization and Melting Behavior of Peptide Nucleic Acid (PNA) Oligonucleotide Chimeras Conjugated to Gold Nanoparticles

Abstract: In this study, Peptide Nucleic Acids (PNA) and PNA-DNA chimeras carrying thiol groups were used for surface functionalization of gold nanoparticles. Conjugation of PNA to citrate stabilized gold nanoparticles destabilized the nanoparticles causing them to precipitate. Addition of a tail of glutamic acid to the PNA prevented destabilisation of the nanoparticles but resulted in loss of interaction with complementary sequences.Importantly, PNA-DNA chimeras gave stable conjugates with gold nanoparticles. The hybri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…AuNP size Centrifugation parameter Application/Study Slot and Geuze [25] 15.5 nm 15,000g for 45 min as probes for immunoelectron microscopy Fleming and Walt [35] 14.5 nm Centrifugation (thrice) as substrates for biochemical assays Hazarika et al [23] 15 nm 20,800g for 20 min (twice) functionalized with DNA for biodetection Kim and Lee [36] 55e65 nm 3500 rpm for 2 h coated with hydrogels for drug delivery Lin et al [37] 17.1 nm 15,700g for 10 min (twice) functionalized with neutral and positively charged thiols for better optical sensitivity Murphy et al [38] 13 nm 13,200 rpm for 30 min (twice) linked with oligonucleotides for gene analysis Schneider and Decher [21,39] 13.5 nm 7000 rpm for 3 h coated with polyelectrolytes for biomedical applications Kim et al [40] 30 nm 16,800g for 30 min (twice) coated with PEG as contrast agent for imaging Liang et al [41] 17 nm 11,930g for 20 min conjugated with DNA for biodetection McMahon and Emory [42] 45, 75 and 100 nm 5500 g for 15 min (thrice) functionalized with mercaptoacetic acid and attached with dicyclohexylamine for phase transfer to organic solvents Wang et al [43] 20 nm high-speed centrifugation fabrication of Au/PVP nanofiber composites Wybranowski et al [44] 24 nm 6000 rpm for 20 min coated with serum proteins for drug delivery Eck et al [45] 15 nm 16,000g for 30 min coated with PEG as labeling agent for cancer tissues Diegoli et al [46] 15 nm 3500 rpm for 10 min interaction with naturally occurring organic macromolecules Gomes et al [47] 11.5 nm 30,000g for 25 min for preparation of bionanoconjugates Guan et al [48] 18 nm 8000 rpm for 30 min for detection of Pb 2þ He et al [49] 16, 20, 28, 38, 43 and 55 nm 2000 rpm for 2 h coated with PEG as fluorescent probes for cancer cell imaging Sonavane et al [50] 15, 50, 100 and 200 nm 40,000 rpm for 30 min (thrice) examine effects of size on biodistribution via injection Stakenborg et al [51] 14, 22, 30 and 35 nm centrifugation (thrice) functionalized with DNA for molecular diagnostics Wulandari et al [15] 20 nm 10,000 rpm for 30 min (few times) examine structure of adsorbed citrates Abdulla-Al-Mamun et al [52] 22 nm high-speed (twice) as photothermal agent to kill epithelial carcinoma cells Brun et al [53] 37.5 nm 2300g for 20 min (twice) as radio-sensitizers for cancer treatment Dobrovolskaia et al [54] 30 and 50 nm 18,000...…”
Section: Sourcementioning
confidence: 99%
“…AuNP size Centrifugation parameter Application/Study Slot and Geuze [25] 15.5 nm 15,000g for 45 min as probes for immunoelectron microscopy Fleming and Walt [35] 14.5 nm Centrifugation (thrice) as substrates for biochemical assays Hazarika et al [23] 15 nm 20,800g for 20 min (twice) functionalized with DNA for biodetection Kim and Lee [36] 55e65 nm 3500 rpm for 2 h coated with hydrogels for drug delivery Lin et al [37] 17.1 nm 15,700g for 10 min (twice) functionalized with neutral and positively charged thiols for better optical sensitivity Murphy et al [38] 13 nm 13,200 rpm for 30 min (twice) linked with oligonucleotides for gene analysis Schneider and Decher [21,39] 13.5 nm 7000 rpm for 3 h coated with polyelectrolytes for biomedical applications Kim et al [40] 30 nm 16,800g for 30 min (twice) coated with PEG as contrast agent for imaging Liang et al [41] 17 nm 11,930g for 20 min conjugated with DNA for biodetection McMahon and Emory [42] 45, 75 and 100 nm 5500 g for 15 min (thrice) functionalized with mercaptoacetic acid and attached with dicyclohexylamine for phase transfer to organic solvents Wang et al [43] 20 nm high-speed centrifugation fabrication of Au/PVP nanofiber composites Wybranowski et al [44] 24 nm 6000 rpm for 20 min coated with serum proteins for drug delivery Eck et al [45] 15 nm 16,000g for 30 min coated with PEG as labeling agent for cancer tissues Diegoli et al [46] 15 nm 3500 rpm for 10 min interaction with naturally occurring organic macromolecules Gomes et al [47] 11.5 nm 30,000g for 25 min for preparation of bionanoconjugates Guan et al [48] 18 nm 8000 rpm for 30 min for detection of Pb 2þ He et al [49] 16, 20, 28, 38, 43 and 55 nm 2000 rpm for 2 h coated with PEG as fluorescent probes for cancer cell imaging Sonavane et al [50] 15, 50, 100 and 200 nm 40,000 rpm for 30 min (thrice) examine effects of size on biodistribution via injection Stakenborg et al [51] 14, 22, 30 and 35 nm centrifugation (thrice) functionalized with DNA for molecular diagnostics Wulandari et al [15] 20 nm 10,000 rpm for 30 min (few times) examine structure of adsorbed citrates Abdulla-Al-Mamun et al [52] 22 nm high-speed (twice) as photothermal agent to kill epithelial carcinoma cells Brun et al [53] 37.5 nm 2300g for 20 min (twice) as radio-sensitizers for cancer treatment Dobrovolskaia et al [54] 30 and 50 nm 18,000...…”
Section: Sourcementioning
confidence: 99%
“…The hybridisation and melting behaviour for PNA-DNA chimera coated gold nanoparticles was reported by Murphy et al 226 PNA-DNA chimeras consisted of seven DNA nucleotides linked to five PNA bases and a 5 0 terminal thiol modification was used to tether the chimeras to the gold nanoparticles. The hybridisation and melting properties of complexes formed between these chimera-gold nanoparticles and DNA-gold nanoparticles were studied using UV-Vis melting, and it was observed that the PNA-DNA chimera melting profiles were sharper than the corresponding DNA-gold nanoparticles complexes.…”
Section: Peptide Nucleic Acidsmentioning
confidence: 89%
“…There are many similarities between MOR and PNA, such as their nonionic backbones and high affinity for complementary DNA or RNA sequences; however, MOR is relatively cheap to produce and highly soluble in aqueous solutions 24. Unlike the PNA–gold NP conjugates, which are difficult to prepare and unstable in aqueous solutions,25–27 the MOR–gold NP conjugates (NP average diameter ≈40 nm) have been prepared successfully and the functionalized NPs disperse well in a 5.0 m M phosphate buffer solution (Supporting Information (SI), Figure S1). We found that, in order to obtain stably dispersed conjugates, it is important to minimize the nonspecific adsorption of MOR strands on the NPs.…”
Section: Methodsmentioning
confidence: 99%